Angiotensin and mineralocorticoid receptor antagonism attenuates cardiac oxidative stress in angiotensin II‐infused rats. (November 2015) - Minas, Jacqueline N; Thorwald, Max A; Conte, Debra; Vázquez‐Medina, Jose‐Pablo; Nishiyama, Akira; Ortiz, Rudy M
Summary Angiotensin II (Ang II) and aldosterone contribute to hypertension, oxidative stress and cardiovascular damage, but the contributions of aldosterone during Ang II‐dependent hypertension are not well defined because of the difficulty to assess each independently. To test the hypothesis that during Ang II infusion, oxidative and nitrosative damage is mediated through both the mineralocorticoid receptor (MR) and angiotensin type 1 receptor (AT1), five groups of Sprague–Dawley rats were studied: (i) control; (ii) Ang II infused (80 ng/min × 28 days); (iii) Ang II + AT1 receptor blocker (ARB; 10 mg losartan/kg per day × 21 days); (iv) Ang II + mineralocorticoid receptor (MR) antagonist (Epl; 100 mg eplerenone/day × 21 days); and (v) Ang II + ARB + Epl (Combo; × 21 days). Both ARB and combination treatments completely alleviated the Ang II‐induced hypertension, whereas eplerenone treatment only prolonged the onset of the hypertension. Eplerenone treatment exacerbated the Ang II‐mediated increase in plasma and heart aldosterone 2.3‐ and 1.8‐fold, respectively, while ARB treatment reduced both. Chronic MR blockade was sufficient to ameliorate the AT1‐mediated increase in oxidative damage. All treatments normalized protein oxidation (nitrotyrosine) levels; however, only ARB and Combo treatments completely reduced lipid peroxidation (4‐hydroxynonenal) to control levels. Collectively, these data suggest that receptor signalling, and not the elevated arterial blood pressure, is the principal culprit in the oxidative stress‐associated cardiovascular damage in Ang II‐dependent hypertension.